2022
DOI: 10.13057/oceanlife/o060203
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of aboveground biomass and carbon stock in Damas Beach, Trenggalek District, East Java, Indonesia

Abstract: Abstract. Nur AAI, Arifiani KN, Ramadhandi AR, Sabrina AD, Nugroho GD, Kusumaningrum L, Ramdhun D, Bao TQ, Yap CK, Budiharta S, Setyawan AD. 2022. Estimation of aboveground biomass and carbon stock in Damas Beach, Trenggalek District, East Java, Indonesia. Indo Pac J Ocean Life 6: 103-109. Vegetation plays a vital role in providing environmental services in the form of storing carbon which can mitigate climate change. This study aimed to calculate Aboveground Biomass (AGB) and carbon stock in Damas Beach, Tren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The cumulative AGB in AG-SS was 140.93 ton.ha -1 , while AG-SSB was 127.98 ton.ha -1 . Comparatively, Nur et al (2022) reported a distinct AGB value of 336.37 ton.ha -1 , which differs from the results of this study. Consequently, concerning the AGB in the AG-SS and AG-SSB, this study's findings were smaller than those reported by Nur et al (2022).…”
Section: Aboveground Biomass (Agb)contrasting
confidence: 99%
See 1 more Smart Citation
“…The cumulative AGB in AG-SS was 140.93 ton.ha -1 , while AG-SSB was 127.98 ton.ha -1 . Comparatively, Nur et al (2022) reported a distinct AGB value of 336.37 ton.ha -1 , which differs from the results of this study. Consequently, concerning the AGB in the AG-SS and AG-SSB, this study's findings were smaller than those reported by Nur et al (2022).…”
Section: Aboveground Biomass (Agb)contrasting
confidence: 99%
“…Compared with this study, the total AGC in agroforestry (131.31 ton.ha -1 ) and POP (100.89 ton.ha -1 ) in East Luwu was greater than in Gunung Mas. Notably, this study's total AGC of agroforestry was lower than that Nur et al (2022) reported from Trenggalek, East Java (168.18 ton.ha -1 ). Meanwhile, the total AGC of POP in this study was greater than the report of Khasanah et al (2015) from mineral soils in various regions of Indonesia (35.28 ton.ha -1 ).…”
Section: Potential Carbon Storagecontrasting
confidence: 85%
“…The capacity of a forest as a carbon sink can be referred to from the Above-Ground biomass (AGB) stored by forest vegetation (Ketterings et al 2001;Nur et al 2022). Carbon storage estimation helps gather data relevant to Greenhouse Gas (GHG) reduction (Adame et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Such greenhouse gases are then trapped in the atmosphere, thereby increasing the earth's temperature (Latuconsina 2010). One of the efforts to reduce carbon dioxide levels in the atmosphere and the oceans is by using vegetation on terrestrial and marine ecosystems to absorb and store carbon in the form of living biomass (Wahyudi and Yona 2017;Nur et al 2022). In marine ecosystems, the vegetation consists of low-level and higher-level plants with habitats in the ocean and coast (Duarte et al 2005).…”
Section: Introductionmentioning
confidence: 99%